Explaining Human Recreational Use of ‘pesticides’: The Neurotoxin Regulation Model of Substance Use vs. the Hijack Model and Implications for Age and Sex Differences in Drug Consumption - Hagen, Edward H.; Roulette, Casey J.; Sullivan, Roger J. (Frontiers in Psychiatry, 2013)
Most globally popular drugs are plant neurotoxins or their close chemical analogs. These compounds evolved to deter, not reward or reinforce, consumption. Moreover, they reliably activate virtually all toxin defense mechanisms, and are thus correctly identified by human neurophysiology as toxins. Acute drug toxicity must therefore play a more central role in drug use theory. We accordingly challenge the popular idea that the rewarding and reinforcing properties of drugs "hijack" the brain, and propose instead that the brain evolved to carefully regulate neurotoxin consumption to minimize fitness costs and maximize fitness benefits. This perspective provides a compelling explanation for the dramatic changes in substance use that occur during the transition from childhood to adulthood, and for pervasive sex differences in substance use: because nicotine and many other plant neurotoxins are teratogenic, children, and to a lesser extent women of childbearing age, evolved to avoid ingesting them. However, during the course of human evolution many adolescents and adults reaped net benefits from regulated intake of plant neurotoxins.